USE OF ELEMENTS OF MORAL-AESTHETIC EDUCATION IN RUSSIAN LANGUAGE LESSONS (International journal of artificial intelligence, 2025)
Moral and aesthetic education plays an important role in ensuring that students not only acquire knowledge, but also form spiritual values, develop aesthetic taste and grow as individuals. Through Russian language lessons, students not only learn the language, but also accept moral and aesthetic values through culture, literature and art. The use of works of art, poetry, stories and other literary materials in the lesson process awakens students' emotions and encourages them to think about moral issues.